PRELIMINARY SPECTROSCOPIC STUDY OF FE-BEARING CLAY MINERALS IN ALTERED PILLOW LAVAS FROM LAMIA AREA, GREECE1 - Katranidou, B.; Godelitsas, A.; Sanakis, I. (Bulletin of the Geological Society of Greece, 2016)
Geological material, of greenish color, filling interspaces in altered Triassic pillow lavas of Lamia area (central Greece) was studied, for the first time in the literature. According to XRD and SEM-EDS data it predominantly consists of calcite, zeolites and clay minerals. The zeolites concern thomsonite and analcime. The clay minerals, on the basis of XRD, FTIR and Mössbauer spectroscopic measurements, constitute a Fe-bearing phase of the illlite-glauconite-celadonite group (most likely Fe-illite).